The Non-Literate ‘Other’: The Gendered Narratives of Indian and Pakistani Female Migrant Spouses with emerging English language and literacy skills - Bowman, Alicia (2022)
Adult migrant women with limited formal schooling or emerging English language and literacy skills (known as LESLLA learners) face formidable challenges not only in their personal lives, but also in their efforts to improve their English language and literacy skills in a hyper-literate society that expects migrants to be proficient in the language to demonstrate their willingness to integrate and belong. The presence of these learners in institutions where practitioners are skilled at teaching students from either literacy-based cultures or those already literate in a language other than English, presents various challenges for Further Education (FE) lecturers. Despite these challenges, LESLLA learners remain an under-researched group of students in Second Language Acquisition (SLA) and English Language Teaching (ELT) studies, in particular with regards to research that focuses on LESLLA women, learners who have been discursively produced within the wider media and policy landscape as passive victims of oppression in need of empowerment; incapable or ignorant learners; and migrants reluctant to learn English.